THE EFFECT OF EDUCATION, INCOME AND EXPERIENCE ON EMPLOYEE ACHIEVEMENT AT SAM RATULANGI UNIVERSITY - Tintingon, Glorya p.; Kindangen, Paulus; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Nowadays manpower as a human resource has a very important role because the performance of employees as human resources can affect other factors. Realizing that humans are a determining factor and become the center of attention in every operational activity, a company or an agency is required to manage human resources so that the expected goals can be achieved through an orientation on the use of human resources effectively and efficiently. This research is using a quantitative approach. To collect the research data, primary data collection was used through questionnaires. A questionnaire is a research instrument consisting of a series of questions (or other types of prompts) for the purpose of gathering information from respondents. From the results above Education are not able to influence Employee Achievement at Sam Ratulangi University, while Income and experience are able to influence Employee Achievement at Sam Ratulangi University. This test shows that together Income and Experience on employee may affect the employee achievement at Sam Ratulangi University. For the next writer is expected to add other variables for used as an indicator in further research. This is because it still is variables that affect work performance that have not found by the author. For the next researchers also must take the approach and use other data analysis so that it will produce better research.Â Keywords: employee achievement, education, income, experience